Chronic kidney disease: definition, classification, diagnostics, and treatment - Zh. D. Kobalava; S. V. Villevalde; M. A. Efremovtseva (Российский кардиологический журнал)
Cardiovascular disease (CVD) is the leading cause of death in patients with chronic kidney disease (CKD). At the same time, CKD is an independent risk factor of CVD and mortality. CVD and CKD share common conventional risk factors (such as arterial hypertension, diabetes mellitus, obesity, and dyslipidemia). The combination of CVD and CKD is associated with such non-conventional renal risk factors as hyperhydratation, anemia, phosphorus and calcium metabolism disturbances,systemic inflammation,  and hypercoagulation, which can also influence the development and pathogenesis of CVD. High prevalence of renal dysfunction and adverse prognostic role of reduced glomerular filtration rate (GFR) and albuminuria justified the development of the universal therapeutic strategy for CKD patients. The latest version of these recommendations was published in 2013, as a part of the KDIGO (Kidney Disease Improving Global Outcomes) initiative. The latest KDIGO recommendations classify CKD not only by GFR categories, but also by albuminuria levels, which provides an opportunity to stratify patients by their complication risk. The new classification is based on the evidence demonstrating that the risks of total and cardiovascular mortality, acute renal damage, and CKD progression substantially differ by the levels of urinary albumin excretion, regardless of GFR values. The need for early diagnostics of renal and cardiovascular dysfunction, in order to stratify risk levels and define the therapeutic strategy and tactics, is also reflected by the updates of the national and international recommendations on arterial hypertension, atherosclerosis, and cardiovascular prevention.